A cadaveric validation of a method based on impact analysis to monitor the femoral stem insertion. (March 2020) - Dubory, Arnaud; Rosi, Giuseppe; Tijou, Antoine; Lomami, Hugues Albini; Flouzat-Lachaniette, Charles-Henri; Haïat, Guillaume
Abstract: The success of cementless hip arthroplasty depends on the primary stability of the femoral stem (FS). It remains difficult to assess the optimal impaction energy to guarantee the FS stability while avoiding bone fracture. The aim of this study is to compare the results of a method based on the use of an instrumented hammer to determine the insertion endpoint of cementless FS in a cadaveric model with two other methods using i) the surgeon proprioception and ii) video motion tracking. Different FS were impacted in nine human cadaveric femurs. For each configuration, the number of impacts realized when the surgeon felt that the FS was correctly inserted was noted N surg . For each impact, the insertion depth E was measured and an indicator D was determined based on the time-variation of the force. The impact number N vid (respectively N d ), corresponding to the end of the migration phase, was estimated analyzing the evolution of E (respectively D ). The respective difference between N surg, N vid and N d was similar and lower than 3 for more than 85% of the configurations. The results allow a validation of the use of an impact hammer to assess the moment when the surgeon should stop the impaction, paving the way towards the development of a decision support system to assist the surgeon.